Kepadatan Tungau Debu Rumah Pada Debu Kasur dan Karpet di Salah Satu Pondok Pesantren Sleman Yogyakarta - Arsusanti, Aprilia; Putri, Novita Eka; Shafriani, Nazula Rahma (Universitas Mohammad Husni Thamrin, 2025)
House Dust Mites (HDM) are microscopic parasites often found in dust in the house,especially mattresses and carpets. This study was conducted with the aim of determiningthe density level of DPM in mattress and carpet dust at the One Satu Islamic Boarding School in Sleman, Yogyakarta, and to determine the relationship between HDM density and hygiene behavior. This research method uses observational with a cross-sectional design. HDM examination uses the flotation method with saturated NaCl. The results of this study showed that carpet and mattress dust samples were positive for HDM and had an average density that was relatively low. The density of HDM on carpets was higher at44.07/gr than mattress dust at 27.2/gr. The growth and development factors of HDM are supported by environmental factors such as temperature, humidity, and dense population. In addition, this study found a significant relationship with a p-value (0.005) between hygiene behavior, such as the habit of drying mattresses/carpets and washing sheets, with the density evel of HDM